A forgotten tributary of the Danube – The Vajas River - Pánya, István (Geographica Pannonica, 2021)
During the examination of the historical geography of the Danube-Tisa Interfluve, the reconstruction of the medieval landscape was carried out, within which the channel conditions of the main watercourses were sketched. The most important medieval tributary of the Danube - the Vajas River - could be located based on historical maps, medieval and modern written sources. During the research, it turned out - based on our sources so far – that there was no tributary called Vajas on the right side of the Danube. Only the tributaries/branches on the left side of the river were called Vajas. The Vajas River was not uniform but consisted of at least four sections in an area of about 140 km from Kalocsa to Plavna.
Keywords: medieval Danube, Vajas River, medieval environment, historical geography